2021
DOI: 10.3390/coatings11091012
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Solutions for Stagnation-Point Flow of Unsteady Carreau Fluid along a Permeable Stretching/Shrinking Sheet with Non-Uniform Heat Generation

Abstract: The aim of the present study was to explore the effect of a non-uniform heat source/sink on the unsteady stagnation point flow of Carreau fluid past a permeable stretching/shrinking sheet. The novelty of the flow model was enhanced with additional effects of magnetohydrodynamics, joule heating, and viscous dissipation. The nonlinear partial differential equations were converted into ordinary differential equations with the assistance of appropriate similarity relations and were then tackled by employing the Ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In addition, the values N 1 and N 2 are set to 1. The associated boundary conditions are taken as [52,55]:…”
Section: Statement Of Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the values N 1 and N 2 are set to 1. The associated boundary conditions are taken as [52,55]:…”
Section: Statement Of Problemmentioning
confidence: 99%
“…Hussain et al [54] studied non-uniform heat generation in Carreau fluid across nonlinear elongating cylinder utilizing shooting method. Yang et al [55] examined multiple solution stagnation point flow of Carreau fluid with non-uniform heat generation using RK-4 and shooting method. Mandal and Pal [56,57] analyze entropy generation with magneto-hydrodynamic effect in hybrid nanofluids, carbon nanotubes flow nonlinear radiation effect and variable thermophysical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Al-Amri and Muthtamilselvan (2020) focused on the magneto SPF of nanofluid along with microorganisms across a stretching sheet subjected to radiation effect. The unsteady dissipative flow of Carreau fluid toward an stagnaton-point (SP) across a stretching/shrinking sheet with irregular heat source/sink and magnetic effects was inspected by Yang et al (2021). They found that the velocity distribution increases due to the magnetic number for the stable outcome and declines for the second branch outcome.…”
Section: Introductionmentioning
confidence: 99%
“…The well-known 4th order Runge-Kutta derived shooting approach is utilized to examine the influences of numerous prominent flow factors and various kinds of nanomaterials on the velocity curve, energy estimation, drag friction coefficient and heat flux. Since, the 4th order Runge-Kutta scheme has been utilized in numerous examinations as a strong computational approach (Rahman et al [20], and Yang et al [21] utilized this scheme to analyze the thermal and mass transport in the boundary layer scheme with various prominent conditions). The graphical results are displayed and explain for the several influencing factors in details.…”
Section: Introductionmentioning
confidence: 99%